PENGARUH VARIASI KOMPOSISI PAKAN OLAHAN LIMBAH IKAN TERHADAP PERTUMBUHAN BURUNG PUYUH SEBAGAI SUMBER BELAJAR LKPD PEMBELAJARAN MATERI PERTUMBUHAN DAN PERKEMBANGAN - Didik Andrianto; HRA Mulyani; Handoko Santoso (EDUBIOLOCK, 2025)
The objectives of this study were 1) To determine the effect of variations in the composition of the use of processed fish waste feed on bird growth (Coturnix coturnix japonica), 2) To determine the variation of feed composition that gives the best effect on the growth of quail (Coturnix coturnix japonica) 3) To determine the results of this study worthy of being used as a Biology learning resource in the form of student activity sheets (LKPD). This type of research is experimental research using a completely randomized design (RAL). In this study using 1 dick 3 treatments namely, P0 (50% centrate feed & 50% bran feed), P1 (Feed 10% fishmeal, 45% bran & 45% Concentrate), P2 (Feed 20% fishmeal + 40% bran & 40% Concentrate), and P3 (Feed 30% fishmeal + 35% bran & 35% Concentrate) each treatment was given 4 replicates. The parameter observed was quail weight gain (grams). Based on the results of the study, it can be concluded that variations in the composition of processed fish waste feed affect the growth of quails and the second treatment gives the best effect. The results of this study can be used as a biology learning resource with high school class XII growth and development material in the form of LKPD, data obtained from expert validation, with an average material validation score of 92.85%, design validation 93.75%.